2016
DOI: 10.1038/srep19328
|View full text |Cite
|
Sign up to set email alerts
|

Novel Methods of Determining Urinary Calculi Composition: Petrographic Thin Sectioning of Calculi and Nanoscale Flow Cytometry Urinalysis

Abstract: Accurate determination of urinary stone composition has significant bearing on understanding pathophysiology, choosing treatment modalities and preventing recurrence. A need exists for improved methods to determine stone composition. Urine of 31 patients with known renal calculi was examined with nanoscale flow cytometry and the calculi collected during surgery subsequently underwent petrographic thin sectioning with polarized and fluorescent microscopy. Fluorescently labeled bisphosphonate probes (Alendronate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…The ready availability of the FDA-approved probe components makes the alendronate-based Fluorescein-BP conjugate 1 particularly attractive for development and human translation as a method for the detection of calcification. Recently the Leong group reported the use of Fluorescein-BP 1 for the study of urinary calculi 15 ; although the fluorescence intensity of the probe in the presence of macroscopic calcium oxalate (CaOx) was found to be relatively moderate.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ready availability of the FDA-approved probe components makes the alendronate-based Fluorescein-BP conjugate 1 particularly attractive for development and human translation as a method for the detection of calcification. Recently the Leong group reported the use of Fluorescein-BP 1 for the study of urinary calculi 15 ; although the fluorescence intensity of the probe in the presence of macroscopic calcium oxalate (CaOx) was found to be relatively moderate.…”
Section: Resultsmentioning
confidence: 99%
“…Fluorescein-BP was synthesised following the procedure reported by the Leong group 15 . Specificity of the probe towards HAP was shown by incubating Fluorescein-BP with a range of calcium minerals including HAP, calcium pyrophosphate (CaPy), CaOx and calcium phosphate (CaPi).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously demonstrated that alendronate-fluorescein isothiocyanate (FITC), a fluorescently labeled bisphosphonate, binds to oxalate calculi via petrographic thin sections of calcium oxalate kidney stones and to nanocrystals in patient urine samples ( Gavin et al, 2016 ). Pulverized calcium oxalate kidney stones were stained with alendronate-FITC and hydroxyapatite nanoparticles were used as a positive control, revealing a high binding affinity of the alendronate-FITC bisphosphonate probe to calcium oxalate calculi ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Stone samples were collected using either duckbill forceps or an endoscopic grasping basket and deposited directly into a sterile container and stored at −20°C. Patient data, stone and urine analysis data, including oxalate crystal data, were previously presented in an independent report ( Gavin et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%